1996
DOI: 10.1089/end.1996.10.141
|View full text |Cite
|
Sign up to set email alerts
|

Ureteroscopic Retrograde Endopyelotomy for Management of Ureteropelvic Junction Obstruction

Abstract: Despite the success of endopyelotomy, many points are still being debated. Ureteroscopic retrograde endopyelotomy was carried out in 49 adult patients with 39 available for long-term follow-up. Prestinting facilitated instrument passage and reduces morbidity. The average operating time was 90.2 minutes. Two patients underwent elective nephrectomy for poorly functioning kidneys that did not improve after treatment, and one patient underwent urgent nephrectomy for bleeding 26 days postoperatively. Improvement in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…It has also been proven that placement of a ureteral stent 1 to 2 weeks prior to ureteroscopic procedures is an effective means of reducing stricture formation. 19,20 Accordingly, pretreatment soft dilation of the ureteral lumen by a stent should reduce the risk of ischemia with use of the 12F-14F or 14F-16F access sheaths.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been proven that placement of a ureteral stent 1 to 2 weeks prior to ureteroscopic procedures is an effective means of reducing stricture formation. 19,20 Accordingly, pretreatment soft dilation of the ureteral lumen by a stent should reduce the risk of ischemia with use of the 12F-14F or 14F-16F access sheaths.…”
Section: Discussionmentioning
confidence: 99%
“…The success rate of 89-90% [12,13] is thought to be noticeably poorer in patients with crossing vessels [12,13]; however, this is not undisputed [14,15]. Be that as it may, to prevent bleeding complications it is necessary to be familiar with the vascular situation around the UPJ prior to the procedure [3,[16][17][18]. CT angiography is used for this purpose, as it is highly accurate, quick to perform and shows all relevant anatomical structures in relation to one another [3,19,20].…”
mentioning
confidence: 99%
“…Similarly, Thomas and colleagues [Thomas et al 1996] in their series of ureteroscopic endopyelotomy, reported one case of acute postoperative hemorrhage that required nephrectomy. In the present study among 42 cases that underwent ureteroscopic laser endopyelotomy, no single case had significant intra-operative or postoperative hematuria following the procedure.…”
Section: Discussionmentioning
confidence: 89%
“…However, this difference was not statistically significant (p ¼ 0.4). Ureteroscopic endopyelotomy has a success rate ranging from 75 to 100% [Biyani et al 2000;Giddens and Grasso, 2000;Matin et al 2000;Conlin and Bagley, 1998;Tawfiek et al 1998;Thomas et al 1996]. In one of the largest series, ureteroscopic endopyelotomy showed a success [Cheung et al 2001].…”
Section: Discussionmentioning
confidence: 99%